Organic matter in the samples withdrawn for clay and clay plus silt and its effect in mechanical analysis by the pipette method - Jorge, José Antonio; Lepsch, Igo Fernando (Pesquisa Agropecuaria Brasileira, 2014)
The effects of three dispersing agents for mechanical analysis (NaOH, NaOH + Sand and Calgon) on the solubility of the organic matter of A horizons from Latossols, B-textural and Gley soils were studied. Organic matter content on the suspensions were obtained in the sample withdrawn for clay and clay plus silt determinations. In about 80% of the cases the amount of organic matter in the suspension in the sample withdrawn for clay determination was between 50 and 100% from the amount found in the air dried soil samples and between 75 and 100%, in the sample withdrawn for clay plus silt determination. NaOH plus sand lead to higher contents of organic matter in the sample for clay determination, whereas Calgon lead to the lowest contents. Organic matter in the suspension may be detected in some cases as part of the clay or silt fraction increasing their real values. This happens mainly when more violent mechanical shaking processes are used. However, these increases tend to be compensated when clay and silt contents are not expressed on a soil organic matter free basis.
Keywords: dispersing agents; previous treatment; texture